An analysis of the stress levels, influencing factors and countermeasures of kidney transplant recipients in a certain hospital - Jiang, Jingyi; Wu, Lin; Xiong, Leiqun; Zhao, Bin; Tian, Shaoping; Wang, Houzhao; Lv, Xiaoying (Frontiers in Public Health, 2025)
BackgroundKidney transplantation remains the most effective therapeutic intervention, significantly enhancing long-term survival rates and overall well-being. Patients undergoing kidney transplantation face challenges in terms of their physical, psychological and social adaptation, such as anxiety, depression and psychological stress resulting from changes in their lifestyle. Existing studies with insufficient analysis of psychological and social factors and systematic intervention strategies.ObjectiveThis study aims to evaluate the current stress levels status of patients after kidney transplantation. Analyze influencing factors, and explore targeted intervention strategies, with the goal of informing comprehensive patient management and improving long-term outcomes.MethodsA cross-sectional study was conducted, enrolling recipients who underwent kidney transplantation at a tertiary-level hospital in Fujian Province between June 2019 and December 2024. A total of 202 valid questionnaires were collected. Demographic characteristics, disease-related information, and current stress levels were collected through questionnaire surveys. Independent samples t-tests or one-way ANOVA were performed on total stress scores. Variables with p < 0.05 were included in multiple linear regression analysis to assess the combined effects of independent variables on total stress scores.ResultsA total of 202 samples were included. The patients’ total stress score was 57.78 ± 12.73, with an average score of 2.41 ± 0.53 per item. Kidney transplant recipients generally experience moderate stress levels, with financial situation having the highest average score (2.91 ± 1.07), while the mean score for romantic and marital psychology is the lowest (1.86 ± 1.00). The economic situation of the family, factors related to the disease and knowledge of postoperative recovery are important factors that influence the level of stress experienced by patients (p < 0.05), accounting for 48.5% of the variance in stress levels.ConclusionKidney transplant recipients exhibited moderate levels of stress, with economic circumstances representing a predominant source of stress. The economic status of the patient’s family, factors associated with the illness, and knowledge of postoperative recovery had a significant impact on the overall stress levels. To alleviate stress and enhance the quality of life for these patients, it is recommended that financial assistance be provided, enhanced post-transplant management and educational programmes be implemented to promote knowledge about the condition.